Developing Thermodynamics Teaching Method by Using Computer Based Problems Solving With Interactive Thermodynamics Property Tables and Equations - Herawan, Safarudin Gazali; Ab Razak, Juhari; Yusof, Ahmad Anas; Suhaimi, Misha (2005)
Computer based problems solving are the tutorial and assignment that all the problems are solved through individual interactive work with a personal computer. Immediate feedback on errors is provided and the grading is done mostly by the computer. The time frame of problems solving can be set so that most students are able to redo the whole problems or selected one using different sets of the data to achieve mastery level. In courses where computer based problems solving was used, a definite improvement in the problem-solving skills of all the students was observed, while the effort for study very hard and grading was actually reduced. To change conventional learning method, some objectives are needed as a step for develop the interactive program, such as considering related platform for e-learning process, developing databases for thermodynamics property tables, deriving several properties of pure substances based thermodynamics equations, and developing interactive interface for self-help tutorial, on-line quizzes